Public policy and economic competition in Japan : change and continuity in antimonopoly policy, 1973-1995 - Beeman, Michael L., 1966- (Nissan Institute/Routledge Japanese studies series., 2003)
Dr. Beeman analyses the diverse interests of industry, government and other parties to reveal how and why antimonopoly policy has made important inroads yet ultimately failed to gain deep acceptance in Japan.